HUBUNGAN PEMBERIAN ASI DENGAN KEJADIAN IKTERIK FISIOLOGIS PADA BAYI USIA 3-14 HARI DI KLINIK KARTIKA HUSADA DONOMULYO - Oktaviani, Elly Nura; Widiatrilupi, Raden Maria Veronika; Sulistiyah (Maternity and Neonatal : Jurnal Kebidanan, 2025)
ABSTRACT Physiological icteric is yellow in infants aged 3-14 days. One of the causes of physiological iterative is the lack of optimal breastfeeding, health experts recommend breastfeeding mothers with an interval of 3 hours, with a frequency of 8-12 times a day in the first few days. Babies who get enough milk with bilirubin levels tend to be lower than babies who lack breast milk intake. This is caused by several factors, including inadequate breastfeeding frequency and suboptimal breast milk intake. The purpose of this study is to determine the relationship between breastfeeding and the incidence of Physiological Psychology in Infants Aged 3-14 days at Kartika Husada Clinic, Donomulyo. This research method: uses a correlation descriptive method, with a Cross Sectional approach, namely with a single time. The determination of the number of respondents uses the total sampling technique which is equal to the population. So this study used 60 respondents. The respondents who were taken had met the inclusion criteria, and there were no characteristic characteristics of the exclusion criteria. Respondents who were researchers using mothers who gave birth normally and/or were referred by SC to the hospital with babies aged 3-14 days. Results: The results of the Chi Square Test obtained a sig value on the frequency factor, duration and method of breastfeeding less than 0.050 (0.020 on frequency; 0.006 on duration; 0.046 on breastfeeding), a chi-square sig value greater than 0.050 (0.325 on breast milk production; 0.570 on drying the baby), so it can be said that there is a relationship of breastfeeding which includes criteria (breastfeeding frequency, duration of breastfeeding and the correct way of breastfeeding, milk production) with physiological aquatic events, but there was no relationship between the baby's drying and psychological events at the Kartika Husada Donomulyo clinic. In conclusion: there is a relationship between breastfeeding and physiological events at the Kartika Husada Donomulyo clinic